Erosion von Verfassungsvoraussetzungen. Berichte und Diskussionen auf der Tagung der Vereinigung der Deutschen Staatsrechtslehrer in Erlangen vom 1. bis 4. Oktober 2008 The Erosion of Constitutional Requirements. Reports and discussions from the Meeting of the Association of German Constitutional Law Teachers in Erlangen from 1st to 4th of October 2008 - Möllers, Christoph (Veröffentlichungen der Vereinigung der Deutschen Staatsrechtslehrer, 2009)
This volume presents the reports and discussions held at the conference of the "Association of German Constitutional Teachers" in Erlangen from October, 1st to October, 4th, 2008.